Organizational Aspects of Increasing the Efficiency of Water Resource Use Management (In The Case Of Kashkadarya Region) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article presents the results of a survey of river basin territories, the nature of runoff formation and the use of water resources. Modeling of the use of water resources in river basins is presented, criteria for qualitative and quantitative water parameters are established.